2013
DOI: 10.1055/s-0033-1342919
|View full text |Cite
|
Sign up to set email alerts
|

Trends In Acoustic Neuroma Management: A 20-Year Review of the Oxford Skull Base Clinic

Abstract: Objective?To describe the change in the management of acoustic neuromas at one United Kingdom center over a 20-year period and to compare this with what is known regarding trends in practice on a national and international scale. Design, Setting, and Participants?Data was collected prospectively on all patients attending the Oxford Skull Base Clinic between 1990 and 2009. Main Outcome Measures?The proportion of patients managed initially by observation versus radiotherapy versus surgery was recorded for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In tandem with the increasing number of patients, this study has demonstrated a downward trend in the numbers of patients presenting with larger tumours. This trend in diagnosis has meant that there are larger numbers of patients presenting with smaller tumours and there has been a steady decrease in surgically treated patients at our centre, in keeping with previously published findings [ 4 , 12 - 14 ]. As has been seen worldwide, the trend in acoustic neuroma management is to utilise a more conservative approach, with increasing numbers of patients under observation or treated with radiosurgery, and surgery now focusing on preservation of the facial nerve [ 12 ].…”
Section: Discussionsupporting
confidence: 87%
“…In tandem with the increasing number of patients, this study has demonstrated a downward trend in the numbers of patients presenting with larger tumours. This trend in diagnosis has meant that there are larger numbers of patients presenting with smaller tumours and there has been a steady decrease in surgically treated patients at our centre, in keeping with previously published findings [ 4 , 12 - 14 ]. As has been seen worldwide, the trend in acoustic neuroma management is to utilise a more conservative approach, with increasing numbers of patients under observation or treated with radiosurgery, and surgery now focusing on preservation of the facial nerve [ 12 ].…”
Section: Discussionsupporting
confidence: 87%
“…The conception of “wait and scan” is accepted worldwide, especially for the small, primary and sporadic tumor. 14 , 15 , 16 , 17 Radiotherapy is accepted as mainstream method for the patients with surgical contra-indication. 18 , 19 The management strategy becomes individual, which mainly depends on the radiological features (cystic or not, tumor size and extension), the biologic feature (tumor growth rate), the severity of symptoms (ipsilateral and contralateral hearing, facial function, other complications), the patient's age, and the general situation and expectations.…”
Section: Management Goal and Strategymentioning
confidence: 99%
“… 18 , 19 The management strategy becomes individual, which mainly depends on the radiological features (cystic or not, tumor size and extension), the biologic feature (tumor growth rate), the severity of symptoms (ipsilateral and contralateral hearing, facial function, other complications), the patient's age, and the general situation and expectations. 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Management Goal and Strategymentioning
confidence: 99%
“…V estibular schwannomas (VS) are benign intracranial nerve sheath tumors that can grow to impinge on surrounding structures of the cerebellopontine angle. Management of these tumors has evolved over time, [1][2][3] but microsurgical resection remains the only option for tumor removal and is often recommended in the case of rapid tumor growth, impending or progressing hearing loss, or significant mass effect such as brainstem compression or hydrocephalus. With refinement in microsurgical techniques, surgical outcomes continue to improve, and the goals of surgery have shifted from radical resection to preservation of neurologic function.…”
mentioning
confidence: 99%